Dielectric based measurement system for the determination of watermelon internal quality - Sairi, Masniza; Suhaime, Noradira; Abbas, Zulkifly; Mohamed Nafis, Nur Biha; Othman, Zaulia; Mhd Adnan, Amir Syariffuddeen; Shamsulkamal, Amir Redzuan (Penerbit MARDI, 2018)
A dielectric based measurement system was used in the determination of watermelon internal quality, focusing on maturity stage. This technique is based on microwave reflection measurement at watermelon surface using an open-ended coaxial probe with a microwave network analyzer operating in the frequency range from 1.0 to 8.5 GHz. The dielectric and physicochemical properties were measured during the fruit maturity stage from week 6 to 10. The effects of frequency and moisture content on the values of permittivity (dielectric constant, ɛ’ and dielectric loss, ɛ”) were investigated. Mass, volume and SSC values increased, while moisture content and density values decreased with maturity stage (time). Permittivity values decreased with maturity stage, in agreement with theory in which permittivity of moist materials is a function of moisture content, density and frequency. In addition, the dielectric constant at all maturity stages decreased with the increasing frequency suggesting watermelon ɛ’ followed the profile of water ɛ’. The dielectric loss decreased with frequency then increased slightly as frequency approached 8.5 GHz. The turning, known as critical frequency separates the bound and free water molecules. This technique showed potential to determine moisture content, then maturity stage from its dielectric properties.